2016
DOI: 10.1158/1535-7163.mct-15-0692-t
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Phosphoproteomics Reveals Wee1 Kinase as a Therapeutic Target in a Model of Proneural Glioblastoma

Abstract: Glioblastoma (GBM) is the most common malignant primary brain cancer. With a median survival of about a year, new approaches to treating this disease are necessary. To identify signaling molecules regulating GBM progression in a genetically engineered murine model of proneural GBM, we quantified phosphotyrosine mediated signaling using mass spectrometry. Oncogenic signals, including phosphorylated ERK MAPK, PI3K, and PDGFR, were found to be increased in the murine tumors relative to brain. Phosphorylation of C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 14 publications
1
9
0
Order By: Relevance
“…Treatment of cells derived from these tumors with the Wee1 inhibitor MK‐1775 increased DNA damage and lead to apoptotic cell death. Similar results were observed in patient‐derived xenografts treated with this kinase inhibitor . Another study identified a hyperphosphorylation of the kinase SRPK2 and its downstream targets in head and neck squamous cell carcinoma cell lines when compared with an untransformed oral cell line.…”
Section: Introductionsupporting
confidence: 68%
“…Treatment of cells derived from these tumors with the Wee1 inhibitor MK‐1775 increased DNA damage and lead to apoptotic cell death. Similar results were observed in patient‐derived xenografts treated with this kinase inhibitor . Another study identified a hyperphosphorylation of the kinase SRPK2 and its downstream targets in head and neck squamous cell carcinoma cell lines when compared with an untransformed oral cell line.…”
Section: Introductionsupporting
confidence: 68%
“…PKMYT1 serves as a negative modulator of the cell cycle, preventing cells from transforming from G2 to the mitosis phase through 2 pathways [ 15 ]. One is binding of PKMYT1 localized to the cytoplasm to the cDC2/cyclin B complex, which restrains the complex from entering the nucleus [ 16 ]. In addition, PKMYT1 suppresses cDC2 activity by phosphorylating the Thr14/Thr15 residue on cDC2 [ 17 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…AZD1775 is also used in many studies as a probe to interrogate WEE1 biology as it has been described to display high target selectivity, although details on kinome-wide target inhibition have not been reported. We and others have previously observed that AZD1775 does not exhibit anticancer activity just in combination with radiation or chemotherapy but also as a single agent in various tumor types. Such single agent activity has been confirmed in early phase clinical trials and appears to be accompanied by a better safety profile than when AZD1775 is administered in combination with cytotoxic chemotherapy drugs or CHK1 kinase inhibitors. , However, the underlying mechanism for this is not fully understood considering that single agent AZD1775 activity was found to be independent of TP53 mutational status. In addition, a recent medicinal chemistry study reported superior antiproliferative single agent activity of AZD1775 compared to other similarly potent WEE1 inhibitors . We hypothesized that these differences could be the result of differential cellular target profiles.…”
mentioning
confidence: 97%